Design of a peanut moisture detector based on STM32and MATLAB - Yin, Yuanyuan (Emirates Journal of Food and Agriculture, 2018)
The measurement accuracy and repetition rate of the existing peanut moisture detector are poor. To solve this problem, this paper designs a capacitive peanut moisture detector based on the capacitance method. Firstly, the structure of coaxial cylindrical capacitive moisture sensor is optimized. STM32 chip microcomputer is used in the main control chip, and the change in capacitance is transformed to change in frequency by capacitance detection circuit. The temperature and quality of peanut kernel are measured by DS18B20 temperature sensor and weighing sensor respectively. The influence of particle size, moisture content, temperature and volume density on the output differential frequency of capacitance sensor are studied by using the differential frequency method. In the range of moisture content of 4.3%-19.1% and temperature of 10°C-40°C, a mathematical model for the relationship among moisture content, temperature, and differential frequency is established. The prediction test of peanut kernel’s moisture content shows that the measurement error of moisture content is within ±0.5%, indicating that the instrument has high measurement accuracy and repeatability when it is used to detect the moisture content of peanut kernels, and has a wide application prospect.